Inovasi Pengolahan Limbah Jelantah Menjadi Sabun Cuci untuk Kemandirian Ekonomi Kelompok Usaha Bersama - Siti Zahliyatul Munawiroh; Viviane Annisa; Fajar Aji Lumakso; Awaluddin Nurmiyanto; Lutfi Chabib; Yulianto Yulianto; Hartanto Hartanto; Isnaini Pujimagfiroh; Abdul Mu’is Ardiyanto; Erlangga Prabowo; Muhammad Nurur Rifqi (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2026)
In Padukuhan Blekik, Sleman, the majority of residents (70%) still dispose of this waste into drains due to a lack of knowledge regarding environmental impacts and its economic potential. This community service activity aims to educate on the negative impacts of used cooking oil and train the women of the Kelompok Usaha Bersama (KUB) in processing this waste into solid and liquid laundry soap. The methods used included counseling based on a spiritual approach, education of management of Used Cooking Oil, and demonstrations of soap making. The results of the activity showed an increase in environmental awareness and technical skills among participants. Evaluation through pre-test and post-test showed a significant increase in the average score by 79%, from an initial score of 43 to 77. This activity successfully transformed the community's perception of waste into an economically valuable resource and provided skill capital for the economic independence of KUB Blekik.